How the Word "Bilingual" Simplifies Reality: Insights from the Paraguayan Experience. - Pöllänen, Roosa (Journal of Multilingual Theories & Practices, 2025)
This article presents an overview of the current situation of Paraguay's languages, focusing on the Indigenous languages spoken in the territory and their multilingual practices. Using the previous literature on the languages of Paraguay, census data, and legal texts, I show how the myth of Spanish-Paraguayan Guaraní bilingualism has influenced societal perceptions and policies and, as a consequence, how the Indigenous languages have received very little attention in both academic and social contexts. It is argued that by challenging Western ideas of language and bi- and multilingualism, and re-evaluating Western practices of defining and naming languages, a more adequate picture of language use in Paraguay can be achieved, leading to the development of more inclusive language description and planning for the country's Indigenous languages.